A Solid Polymer Electrolyte from Photo-Crosslinked Polytetrahydrofuran and a Cycloaliphatic Epoxide for Lithium-Ion Conduction. (2020) - Genier, Francielli S.; Barna, James; Wang, Jiayue; Biria, Saeid; Hosein, Ian D.
Abstract: We report on the synthesis, properties, and ion conductivity of a solid polymer electrolyte produced from polytetrahydrofuran (PTHF) photo-crosslinked with 3, 4-epoxycyclohexylmethyl 3ʹ, 4ʹ-epoxycyclohexane carboxylate (Epoxy), via an active monomer mechanism that facilitates the reaction of the native hydroxyl and epoxide end-groups. Crosslinked samples were loaded with different quantities of lithium tetrafluoroborate (LiBF4 ) and evaluated by electrochemical spectroscopy impedance (EIS) to determine their ionic conductivity. An increase in lithium salt loading led to an increase in ionic transport, reaching competitive conductivities of up to 10 -3 S/cm at temperatures typical for battery operation. Thermal analysis confirms the amorphous structure and high thermal stability (30-90°). The mechanical analysis shows the materials possess suitable stiffness for applications. The results demonstrate a new synthetic route to tunable crosslinked networks for a broad range of chemical building blocks to achieve high lithium-ion conduction and attain desirable thermal and mechanical properties.